2019
DOI: 10.3892/ijo.2019.4881
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib inhibits vascular endothelial cell proliferation stimulated by anaplastic thyroid cancer cells regardless of BRAF mutation status

Abstract: Anaplastic thyroid cancer (ATC) is a rare refractory disease, frequently associated with BRAF mutations and aberrant vascular endothelial growth factor (VEGF) secretion. The antitumor effects of sorafenib were evaluated, and its mechanisms of action were investigated. Four human ATC cell lines were used: OCUT-4, which possesses a BRAF mutation; OCUT-6 and ACT-1, which carry NRAS mutations; and OCUT-2, which possesses mutations in BRAF and PI3KCA. The viability of Sorafenib was evaluated by MTT assay. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Additionally, cancer can cause unregulated vessel growth by modulating angiogenesis and vasculogenesis, aiding in the proliferation and metastatic spread of cancerous cells. Several cancer therapies, such as the VEGF pathway inhibitors sorafenib and sunitinib, are effective at targeting these processes in cancerous tissue, but also disrupt normal angiogenic processes and are associated with cardiovascular toxicity in patients [ 30 , 31 , 32 ]. There are several existing in vitro models for angiogenesis, such as proliferation assays, tubule formation assays, and organ explant assays [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Zebrafish As a Model For Cardiovascular Diseasementioning
confidence: 99%
“…Additionally, cancer can cause unregulated vessel growth by modulating angiogenesis and vasculogenesis, aiding in the proliferation and metastatic spread of cancerous cells. Several cancer therapies, such as the VEGF pathway inhibitors sorafenib and sunitinib, are effective at targeting these processes in cancerous tissue, but also disrupt normal angiogenic processes and are associated with cardiovascular toxicity in patients [ 30 , 31 , 32 ]. There are several existing in vitro models for angiogenesis, such as proliferation assays, tubule formation assays, and organ explant assays [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Zebrafish As a Model For Cardiovascular Diseasementioning
confidence: 99%
“…In human patients, the efficacy of molecular-targeted therapy has been shown to be limited and to depend on the presence of specific genetic alterations in cancer cells. 5 B-Raf (Rapidly accelerated fibrosarcoma) proto-oncogene (B-RAF) mutation is widely known as an important driver of the aberrant proliferation of cancer cells. 6,7,8 A B-RAF-targeting inhibitor has already been established as an important therapeutic agent in several types of human cancers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Sorafenib activity against ATC cells has been proved both in vitro and in vivo experiments. In the former, Sorafenib reduced proliferation and enhanced apoptosis in several ATC cell lines, regardless of BRAF mutation status [ 39 , 40 ]; in the latter, Sorafenib proved effective in inhibiting the growth of orthotopic ATC xenografts in mice, thus improving their survival [ 39 ]. Preclinical studies suggested that several drugs may exert synergic effect with Sorafenib in reducing ATC cells growth, including metformin [ 41 ].…”
Section: Main Textmentioning
confidence: 99%